High-level expression of IMP-5 carbapenemase owing to point mutation in the -35 promoter region of class 1 integron among Pseudomonas aeruginosa clinical isolates - Brizio, A (2015)
Eight strains of Pseudomonas aeruginosa producing IMP-5 carbapenemases were collected from three Portuguese hospitals. All isolates were epidemiologically unrelated. The bla(IMP-5) gene was inserted into a class I integron previously reported in Acinetobacter baumannii 65FFC. Expression of the the blaIMP-5 gene in P aeruginosa has been shown to be driven by the P, promoter [TTGATA] in which the cytosine was replaced by thymine, which caused an increase in transcription of blaIMP-5 that was confirmed by site-directed mutagenesis. The minimum inhibitory concentrations (MICs) of imipenem for Escherichia coli pGMLA-1 (the recombinant front A. baumannii 65FFC) and E. coli pATG-2 (the recombinant from P. aeruginosa isolates) were 0.5 mg/L and 32 mg/L, respectively. This study reports the spread of a class 1 integron In76 with a new point mutation in the P-1 promoter sequence leading to overproduction of INIP-5. (c) 2005 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.